Sympathoexcitatory Responses to Isometric Handgrip Exercise Are Associated With White Matter Hyperintensities in Middle-Aged and Older Adults - Pearson, Andrew G.; Miller, Kathleen B.; Corkery, Adam T.; Eisenmann, Nicole A.; Howery, Anna J.; Cody, Karly A.; Chin, Nathaniel A.; Johnson, Sterling C.; Barnes, Jill N. (Frontiers in Aging Neuroscience, 2022)
Vascular dysfunction may occur prior to declines in cognitive function and accumulation of neuropathology. White matter hyperintensities (WMH) develop due to cerebral ischemia and elevated blood pressure in midlife. The purpose of this study was to evaluate associations between cardiovascular and cerebrovascular responses to sympathoexcitatory stimuli and WMH burden in cognitively unimpaired middle-aged and older adults. Sixty-eight adults (age = 63 ± 4y, men = 20, women = 48) participated in this study. Participants completed isometric handgrip exercise (IHG) exercise at 40% of maximal voluntary contraction until fatigue followed by a 90s period of post-exercise ischemia. Heart rate (HR), mean arterial pressure (MAP), middle cerebral artery blood velocity (MCAv), and end-tidal CO2 were continuously measured throughout the protocol. Cerebrovascular resistance index (CVRi) was calculated as MAP/MCAv. WMH lesion volume and intracranial volume (ICV) were measured using a FLAIR and T1 scan on a 3T MRI scanner, respectively. WMH fraction was calculated as (WMH lesion volume/ICV)*100 and cubic root transformed. Multiple linear regressions were used to determine the association between cardiovascular and cerebrovascular responses to IHG exercise and post-exercise ischemia and WMH fraction. Multiple linear regression models were adjusted for age, sex, apolipoprotein ε4 status, and total work performed during IHG exercise. During IHG exercise, there were significant increases from baseline in HR (25 ± 12%), MAP (27 ± 11%), MCAv (5 ± 10%), and CVRi (22 ± 17%; P < 0.001 for all). During post-exercise ischemia, HR (8 ± 7%), MAP (22 ± 9%), and CVRi (23 ± 16%) remained elevated (P < 0.001) while MCAv (0 ± 10%) was not different compared to baseline. There was an inverse association between the percent change in HR (r = −0.42, P = 0.002), MAP (r = −0.41, P = 0.002), and CVRi (r = −0.31, P = 0.045), but not MCAv (r = 0.19, P = 0.971) in response to IHG exercise and WMH fraction. There were no associations between responses to post-exercise ischemia and WMH fraction. Lower sympathoexcitatory responses to IHG exercise are associated with greater WMH burden in middle-aged to older adults. These findings suggest that individuals who demonstrate smaller increases in HR, MAP, and CVRi in response to sympathoexcitatory stress have greater WMH burden.